Effects of mindfulness on maternal stress, depressive symptoms and awareness of present moment experience: A pilot randomised trial. (July 2017) - Beattie, Jill; Hall, Helen; Biro, Mary Anne; East, Christine; Lau, Rosalind
Abstract: Objective: To determine the feasibility and acceptability and measure the effects of a mindfulness intervention compared to a pregnancy support program on stress, depressive symptoms and awareness of present moment experience. Design: A pilot randomised trial using mixed methods. Participants and Setting: Forty‐eight women attending a maternity service were randomly allocated to a mindfulness-based or pregnancy support program. Measures: Perceived Stress Scale, Edinburgh Postnatal Depression Scale, Mindfulness Attention Awareness Scale, and Birth Outcomes. Women's perceptions of the impact of the programs were examined via summative evaluation, interviews, diaries and facilitator field notes. Findings: Nine women in the mindfulness program and 11 in the pregnancy support program completed post-program measures. There were no statistically significant differences between groups. Of practical significance, was an improvement in measures for both groups with a greater improvement in awareness of present moment experience for the intervention group. The intervention group reported learning how to manage stressors, fear, anxiety, and to regulate their attention to be more present. The control group reported learning how to calm down when stressed which increased their confidence. Intervention group themes were: releasing stress, becoming aware, accepting, having options and choices, connecting and being compassionate. Control group themes were:managing stress, increasing confidence, connecting, focussing, being accepted, preparing. Key conclusion: The feasibility and acceptability of the intervention was confirmed. Programs decreased women's self-reported stress in different ways. Women in the mindfulness program accepted themselves and their experiences as they arose and passed in the present moment, while those in the control group gained acceptance primarily from external sources such as peers. Implications for practice: Mindfulness programs can foster an internalised locus of self-acceptance which may result in woman becoming less dependent on others for their wellbeing. Adequately powered RCTs, with an active control, long-term follow up and economic evaluation are recommended. Highlights: The feasibility and acceptability of the intervention was confirmed. No statistically significant difference detected between groups on outcome measures. Mindfulness participants released stress through self-awareness and acceptance. Support group participants learnt how to manage and calm down when stressed. Mindfulness may foster internal locus of self-acceptance enhancing self-relience.